LESSON STUDY: AN OPPORTUNITY TO TRANSFORM OSH TEACHING PRACTICE AT SENA - Brito Fuentes, Yuliana Yulieth
The main purpose of this research is to describe the implementation of the Lesson study methodology to transform the Teaching Practice into Occupational Health and Safety competencies, SENA. The study followed the Sociocritical paradigm, with a qualitative, descriptive approach and a design focused on Action Research, with support within the Teaching for Understanding (EpC) framework. From the LS Methodology and from the inputs generated in the development of the practice in its different constitutive actions, it was carried out in seven reflection cycles that allowed observing, documenting, analyzing, and reflecting on the teaching practice in SST, through collaborative work between Peers. Finally, the development of the research impacted both on the development and professional growth of the researcher, as well as on the strengthening of occupational competencies in OSH in the SENA apprentices in the referenced context.